1989
DOI: 10.1002/jnr.490240313
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidate phosphohydrolase in purified rat brain myelin

Abstract: Highly purified myelin from rat brain stem has been shown to contain phosphatidate phosphohydrolase, an enzyme which converts phosphatidate to diacylglycerol. The high levels relative to cytosol and microsomes (17% and 22%, respectively) tended to preclude contamination by these fractions as the source of activity. Additional evidence came from study of repeated purification, mixing experiments, and washing of the myelin with salt and detergent. We conclude that this enzyme, in addition to being widely distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In brain and liver microsomal fractions from adult rats, the PAP 2 form was higher than the PAP 1 form. In this respect, it has been demonstrated that highly-puri®ed myelin from rat brain stem contains PAP 2 and that it is intrinsic to myelin membranes (Vaswani and Ledeen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In brain and liver microsomal fractions from adult rats, the PAP 2 form was higher than the PAP 1 form. In this respect, it has been demonstrated that highly-puri®ed myelin from rat brain stem contains PAP 2 and that it is intrinsic to myelin membranes (Vaswani and Ledeen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least in our hands, the diolein used for preparation of the substrate, and the unlabeled dioleoyl-containing phosphatidate used to dilute the radioactive substrate are more easily dispersed than the corresponding palmitoyl species. Furthermore, the activities of some isozymes of PAP have been reported to be higher when measured by determination of phosphate released from dioleoyl-phosphatidate as compared to dipalmitoyl-phosphatidate (e.g., [15][16][17][18]. Confirming this, using both the diacylglycerol-and the phosphate determination method, we have found the activity of rat liver cytosolic PAP, purified by hydroxylapatite chromatography, to be 2-2.5-fold higher with dioleoyl-phosphatidate than with the dipalmitoyl substrate.…”
Section: Resultsmentioning
confidence: 99%